The tapestry of Halal-related projects in IIUM – the funding and its outputs - Hashim, Yumi Zuhanis Has-Yun; Azmi, Atiqah; Ahmad, Anis Najiha; Samsudin, Nurhusna; Abbas, Phirdaous (HH Publisher, 2025)
Understanding of funding trends and its outputs can assist stakeholders in making informed decisions that maximizes the value and impact of research and innovation investments. While the trend of research articles related to halal is increasing, there is no report on the trend of funding and its output. This study aims to fill in this gap by identifying the funding trends and outputs of halal-related research projects using the sampling population from the Research Management Centre (RMC) at the International Islamic University Malaysia. Upon obtaining access permission, 59 research projects related to halal were obtained and 41 projects were included after screening. The funding trend over the years (2012–2022) was found to be not linear with a particular decrease during the Covid-19 pandemic. The projects (total of RM3.4million) were funded in the range of RM10K–RM300K mostly by the Ministry of Higher Education (MOHE). Most of the talents nurtured were at Master level. Only 26% of the projects produced intellectual properties. A total of 77 journals were published with 55 % were indexed in either Science (WOS), Scopus, or MyCite. Only one journal article was indexed as Q2 and none was indexed in Q1. No significant correlation was found between the total grant (RM) with total publications. To this end, this study provides insight into areas of priority in halal research and development. This would benefit many stakeholders and enable relevant entities to weigh the priorities and future-proof the halal industry through appropriate strategic funding and policy making.